Self-Cross-Linking Characterization of Poly(fumaric-co-itaconic-co-butanediol) - Shao, Fenjuan; Yang, Qun; Lu, Danian (Asian Journal of Chemistry, 2013)
The poly(fumaric-co-itaconic-co-butanediol) [poly(FA-co-IA-co-BD)] was prepared with fumaric acid (FA), itaconic acid (IA) and 1,4-butanediol (BD) by melt polycondensation. The insoluble gel fraction (Qs), as the cross-linking degree of cured poly(FA-co-IA-co-BD) which could be self-cross-linked at high temperature through C=C in it, was got by Soxhlet extraction. The properties were investigated by FT-IR, 1H NMR, DSC and XRD. The results indicated that Qs increased with itaconic acid under the same treating condition. When the mole ratio of fumaric acid and itaconic acid approached to 1, the polyester had the highest Qs (78.13 %) and the maximum rate constant k (0.2552 s-1) after being treated at 150 ºC for 20 min. As Qs increased from 0 to 89.01 %, Tm decreased from 77.5 to 60.1 ºC, DHm and the crystallinity decreased from 36.48 to 23.98 J g-1, 43.10 to 26.30 %, respectively. And the biodegradation of the cross-linked polyesters became worse.